Prevalence of Abnormal Cervical And Vaginal Cytology In HIV-Infected Women Over The Age Of 65 [5N]. (May 2018) - Stewart, Kelsey; Chesnokova, Arina; Syed, Fatima; Levison, Judy
Abstract : INTRODUCTION: HIV-infected women are 10-11 times more likely to develop abnormal cervical cytology compared with HIV uninfected women, elevating the need for Pap smear surveillance. While guidelines for screening exist for HIV-infected women of reproductive age, there is inadequate data to guide care for women over 65. Our research evaluates the prevalence of abnormal cervical cytology/CIN and invasive neoplasia in HIV-infected women over the age of 65 with no history of abnormal Paps to aid in the creation of screening recommendations for this demographic. METHODS: This is a retrospective chart review of records from 2000-2015, from an urban low-income setting. We screened 254 patients, 70 of whom met inclusion criteria: HIV+, age over 65, with at least one pap test after age 65, lacking abnormal cervical/vaginal cytology screening, and lacking history of hysterectomy for non-benign reasons. RESULTS: Of included patients, 17.1% had at least one abnormal pap smear: 41.7% ASCUS/HPV+, 75.0% LSIL, 25.0% HSIL, with 25.0% patients having more than one abnormal result. Of those with abnormal pap, 66.7% had abnormal pathology on follow-up biopsy: 33.3% CIN/VAIN1, 16.7% CIN/VAIN2, 16.7% CIN/VAIN3. No patients had invasive cancer. Median time to first pap test after age 65 was 14.7 months. No demographic factors were significantly associated with abnormal pap. Higher viral load at time of testing was positively associated with abnormal pap. CONCLUSION: Our findings of high rates of abnormal pap tests and subsequent high rates of abnormal pathology suggest that pap tests in women over age 65 may be indicated.